2017
DOI: 10.1016/j.jtusci.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent synthesis, biological evaluation and molecular docking of new spiro-oxindole derivatives

Abstract: A new series of spiro-oxindoles that were identified based upon their ability to inhibit methionine tRNA synthase (PDB ID: 1PFV) and glucosamine-6-phosphate synthase (PDB ID: 1JXA) enzymes in virtual screening was synthesized by a three-component 1,3-dipolar cycloaddition method. The reaction proceeds through the formation of azomethine ylides generated in situ by the decarboxylative condensation of isatin and amino acids with dipolarophile chalcones. These compounds are active against Staphylococcus aureus, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Glucosamine-6-phosphate synthases and Methionyl tRNA synthetases are the key enzymes in the pathway of cell wall chitin synthesis and aminoacylation of tRNA synthesis in fungi. These enzymes were the antifungal targets in an in silico virtual screening by Sapnakumari et al, (2017) 23 , who identified spirooxindoles for their ability to inhibit methionyl tRNA synthetase (PDB ID: 1PFV) and glucosamine-6-phosphate synthase (PDB ID: 1JXA) enzymes which was supported by in vitro antagonism by chemically synthesised spirooxindoles. Similarly, Wu et al, (2015) 24 , have also contributed synthetic spirooxindole derivatives for antifungal activity against phytopathogenic fungi including Fusarium graminearum.…”
Section: Resultsmentioning
confidence: 98%
“…Glucosamine-6-phosphate synthases and Methionyl tRNA synthetases are the key enzymes in the pathway of cell wall chitin synthesis and aminoacylation of tRNA synthesis in fungi. These enzymes were the antifungal targets in an in silico virtual screening by Sapnakumari et al, (2017) 23 , who identified spirooxindoles for their ability to inhibit methionyl tRNA synthetase (PDB ID: 1PFV) and glucosamine-6-phosphate synthase (PDB ID: 1JXA) enzymes which was supported by in vitro antagonism by chemically synthesised spirooxindoles. Similarly, Wu et al, (2015) 24 , have also contributed synthetic spirooxindole derivatives for antifungal activity against phytopathogenic fungi including Fusarium graminearum.…”
Section: Resultsmentioning
confidence: 98%
“…The decarboxylative condensation of isatin and amino acids leading to the generation of azomethine ylides, which could further react with a dipolarophile was explored by Sapnakumari et al ., this time using chalcones as dipolarophile (Scheme 5). This catalyst‐free approach allowed the preparation of a small library (8 examples) in moderate yields [21] …”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…Narayana et al identified a new series of spirooxindoles that could inhibit methionine tRNA synthase (PDB ID: 1PFV) and glucosamine-6-phosphate synthase (PDB ID: 1JXA) enzymes through the virtual screening (Scheme 8). The compounds were efficiently synthesized from isatin, amino acids, and dipolarophile chalcones by a three-component 1,3-dipolar cycloaddition reaction [22]. These compounds were then then found to be active against Raghunathan et al described the synthesis of a series of structurally novel and complex dispiro pyrrolizidines 24 and 25 through the 1,3-dipolar cycloaddition reaction of azomethine ylides generated in situ from secondary amino acids and isatin with bischalcones (Scheme 9) [39].…”
Section: Spiropyrrolidine Oxindolesmentioning
confidence: 99%
“…Spirooxindole (Highlighted in red in Fig. 1) containing compounds have exhibited diverse biological properties, such as anticancer [16][17][18][19][20][21], antimicrobial [22,23], antivirus [24], etc. Representative examples are NITD609 (also known as Cipargamin) [25], CFI-400945 (the first PLK4 inhibitor) [26,27], SAR405838 (MDM2 inhibitor) [28,29] and APG-115 (MDM2 inhibitor) Fig.…”
Section: Introductionmentioning
confidence: 99%